Negotiation in A. Fuadi’s Ranah Tiga Warna (The Land of the Three Colors) - Retno Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Travel writing is one of the literary genres that has received attention today. This paper discusses the work of A. Fuadi’s Ranah Tiga Warna (The Land of the Three Colors) telling the main character’s experience in three lands: Bandung (Indonesia), Amman (Jordan), and Saint Raymont (Canada). This paper is to analyze the negotiation process between ‘the self’ and ‘the other’  experienced by the main character in the third land: Saint Raymont. This uses the concept of  negotiation of ‘the self’ and ‘the other’ by Thompson, and Deleutze’s  and Guattari’s  segmentarity. The results show that the main character can play a flexible interplay between ‘the self’ and ‘the other’, negotiation and accommodation, and even transduction. The successful negotiation process can be seen from the difference and how the main character has willingness to bring the difference to his home country. The main character’s  mention of  ‘return home’ when revisiting Saint Raymond years later becomes the evidence of the successful negotiation as well.Keywords: travel writing, negotiation, the self, the other